How do you find the value of \[2f\left( 1 \right) + 3g\left( 4 \right)\] if \[f\left( x \right) = 3x\] and $g(x) = - 4{x^2}$?
Answer
Verified
443.7k+ views
Hint: Put $x = 1$ in \[f\left( x \right)\] to find the value of \[f\left( 1 \right)\] and put $x = 4$ in \[g\left( x \right)\] to find the value of \[g\left( 4 \right)\]. Then put the values of \[f\left( 1 \right)\] and \[g\left( 4 \right)\] in the expression \[2f\left( 1 \right) + 3g\left( 4 \right)\] to calculate its numerical value.
Complete step by step answer:
According to the question, we have to calculate the value of the expression \[2f\left( 1 \right) + 3g\left( 4 \right)\] and two functions are given to us.
The two functions are \[f\left( x \right) = 3x\] and $g(x) = - 4{x^2}$.
First we will calculate the value of \[f\left( 1 \right)\]. This can be determined by substituting $x = 1$ in \[f\left( x \right)\]. Doing so, this will give us:
$
\Rightarrow f\left( 1 \right) = 3\left( 1 \right) \\
\Rightarrow f\left( 1 \right) = 3{\text{ }}.....{\text{(1)}} \\
$
Next we will calculate the value of \[g\left( 4 \right)\]. In the similar way, this can be obtained by substituting $x = 4$ in \[g\left( 4 \right)\]. So this will give us:
$
\Rightarrow g\left( 4 \right) = - 4{\left( 4 \right)^2} \\
\Rightarrow g\left( 4 \right) = - 4 \times 16 \\
\Rightarrow g\left( 4 \right) = - 64{\text{ }}.....{\text{(2)}} \\
$
As we know, we have to determine the value of the expression \[2f\left( 1 \right) + 3g\left( 4 \right)\]. Thus putting values of \[f\left( 1 \right)\] and \[g\left( 4 \right)\] from the equations (1) and (2) in the expression, we’ll get:
\[
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = 2 \times 3 + 3 \times \left( { - 64} \right) \\
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = 6 - 192 \\
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = - 186 \\
\]
Thus the value of the expression is -186 and this is the answer.
Note: If we have to find the values of the function at the same value of $x$ then we can combine both the functions to solve the expression. For example if we have to determine the value of the expression \[2f\left( 1 \right) + 3g\left( 1 \right)\] or the value of the expression \[2f\left( 4 \right) + 3g\left( 4 \right)\], we can combine both the functions before putting the value of $x$ and it will become:
$
\Rightarrow 2f\left( x \right) + 3g\left( x \right) = 2\left( {3x} \right) + 3\left( { - 4{x^2}} \right) \\
\Rightarrow 2f\left( x \right) + 3g\left( x \right) = 6x - 12{x^2} \\
$
Now we can easily substitute the given value of $x$.
But in expression \[2f\left( 1 \right) + 3g\left( 4 \right)\], we have to determine the values of the functions at different values of $x$. That’s why we need to solve them separately and put those values in the expression as we did above in the solution.
Complete step by step answer:
According to the question, we have to calculate the value of the expression \[2f\left( 1 \right) + 3g\left( 4 \right)\] and two functions are given to us.
The two functions are \[f\left( x \right) = 3x\] and $g(x) = - 4{x^2}$.
First we will calculate the value of \[f\left( 1 \right)\]. This can be determined by substituting $x = 1$ in \[f\left( x \right)\]. Doing so, this will give us:
$
\Rightarrow f\left( 1 \right) = 3\left( 1 \right) \\
\Rightarrow f\left( 1 \right) = 3{\text{ }}.....{\text{(1)}} \\
$
Next we will calculate the value of \[g\left( 4 \right)\]. In the similar way, this can be obtained by substituting $x = 4$ in \[g\left( 4 \right)\]. So this will give us:
$
\Rightarrow g\left( 4 \right) = - 4{\left( 4 \right)^2} \\
\Rightarrow g\left( 4 \right) = - 4 \times 16 \\
\Rightarrow g\left( 4 \right) = - 64{\text{ }}.....{\text{(2)}} \\
$
As we know, we have to determine the value of the expression \[2f\left( 1 \right) + 3g\left( 4 \right)\]. Thus putting values of \[f\left( 1 \right)\] and \[g\left( 4 \right)\] from the equations (1) and (2) in the expression, we’ll get:
\[
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = 2 \times 3 + 3 \times \left( { - 64} \right) \\
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = 6 - 192 \\
\Rightarrow 2f\left( 1 \right) + 3g\left( 4 \right) = - 186 \\
\]
Thus the value of the expression is -186 and this is the answer.
Note: If we have to find the values of the function at the same value of $x$ then we can combine both the functions to solve the expression. For example if we have to determine the value of the expression \[2f\left( 1 \right) + 3g\left( 1 \right)\] or the value of the expression \[2f\left( 4 \right) + 3g\left( 4 \right)\], we can combine both the functions before putting the value of $x$ and it will become:
$
\Rightarrow 2f\left( x \right) + 3g\left( x \right) = 2\left( {3x} \right) + 3\left( { - 4{x^2}} \right) \\
\Rightarrow 2f\left( x \right) + 3g\left( x \right) = 6x - 12{x^2} \\
$
Now we can easily substitute the given value of $x$.
But in expression \[2f\left( 1 \right) + 3g\left( 4 \right)\], we have to determine the values of the functions at different values of $x$. That’s why we need to solve them separately and put those values in the expression as we did above in the solution.
Recently Updated Pages
Using the following information to help you answer class 12 chemistry CBSE
Basicity of sulphurous acid and sulphuric acid are
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Trending doubts
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
Show variation of resistivity of copper as a function class 12 physics CBSE
Electrolysis of dilute H2SO4 generates H2S2O8 What class 12 chemistry CBSE
Figure shows a conducting loop ABCDA placed in a uniform class 12 physics CBSE
Explain with a neat labelled diagram the TS of mammalian class 12 biology CBSE
The first general election of Lok Sabha was held in class 12 social science CBSE